APPLICATION OF PCR TECHNIQUES FOR TB DIAGNOSIS AT THE INSTITUTE OF NUCLEAR MEDICINE, MOLECULAR BIOLOGY & ONCOLOGY (INMO) - UNIVERSITY OF GEZIRA, SUDAN - Gasmelseed, Nagla; Mergani, Adil; Abass Elimam, Mutaz; Elamin Mohamed, Mazin; Mohamed Dafalla, Ameer; Eltahir, Ahmed; Elwali, Nasreldin (Gezira Journal of Health Sciences; Vol 5 No 1 (2009), 2009)
Traditional methods for laboratory diagnosis of tuberculosis (TB) may require weeks, and delays can impede treatment and control efforts. Nucleic acid amplification (NAA) tests, such as polymerase chain reaction (PCR) and other methods for amplifying DNA and RNA, may facilitate rapid detection of microorganisms. This study emphasized our three years experience in the diagnosis of TB on clinical samples using the PCR method. Among 531 patients with suspected TB, 112 (21.3%) were positive by PCR, while 419 (78.7 %) were negative. The specimens collected from TB suspected patients were sputum, blood, ascitic fluid, pleural fluid, and gastric wash. Blood samples showed high positive results 15/41 (34%) in comparison with sputum samples which is the most frequent sample 64/ 285 (22.3%). Gastric wash samples reported low rate of positive result 1/30 (3.3%). This rapid and sensitive test compared with the other cultural and microscopic tests have now been incorporated into our laboratory practice allowing the physicians to manage proper diagnosis and drug regimens.